Ultraviolet light and polyethylene glycol as environmental cleaning agents to reduce contamination of Pseudogymnoascus destructans in bat hibernacula - Alyssa J. Stulberg; Tina L. Cheng; Katy L. Parise; Kaleigh J.O. Norquay; Quinn E. Fletcher; Rebecca L. Mau; Daniel L. Lindner; Jeffrey T. Foster; Barrie E. Overton; Winifred F. Frick; Craig K.R. Willis (PLoS ONE, 2026)
Pathogens that persist in an environmental reservoir can drive host populations to extinction because host abundance does not limit pathogen survival or reproduction. Fungal pathogens are of particular conservation concern because many fungi are generalists that persist in the environment. One example is Pseudogymnoascus destructans , the causative agent of white-nose syndrome (WNS), which has caused severe declines in hibernating bat populations across North America. Treatment of environmental reservoirs could help reduce transmission of P. destructans , and thus, reduce bat population declines from WNS. We tested the efficacy of two environmental cleaning agents, ultraviolet-C radiation and polyethylene glycol, in three mines where P. destructans established an environmental reservoir and caused declines in winter colony size of hibernating bats in Ontario, Alabama, and Arkansas. We observed considerable variation between sites but, based on our experimental design, treatments did not reduce environmental P. destructans prevalence or load and there was no consistent pattern in response to the treatments across mines. More encouragingly, treatments did not impact non-target fungi or bacteria. Our results could reflect aspects of our experimental design, including relatively small treatment cells and the lack of an available assay to assess viability of P. destructans from swab samples. Among-site variation we observed, combined with positive results of these treatments in other studies, suggest that site-specific management responses may be important for reducing impacts of white-nose syndrome on bat populations.